Упростите выражение: (m+1/m-2) : (1/m-1) Найдите, при каком значении m значение выражения равно (-4) .

akyngazy96 akyngazy96    3   06.11.2020 12:32    18

Ответы
максим1715 максим1715  06.12.2020 12:33

Объяснение:

\frac{m + 1}{m - 2} \div \frac{1}{m - 1} = \frac{m + 1}{m - 2} \times \frac{m - 1}{1} = \frac{(m + 1)(m - 1)}{m - 2} = \frac{ {m}^{2} - 1}{m - 2}

2.

\frac{ {m}^{2} - 1}{m - 2} = 4

ОДЗ: m-2≠0

m≠2

m²-1=-4(m-2)

m²-1=-4m+8

m²-1+4m-8=0

m²+4m-9=0

D=b²-4ac=4²-4×1×(-9)=16+36=52

m1;2= \frac{-b± \sqrt{D} }{2a} = \frac{ - 4± \sqrt{52} }{2} = \frac{ - 4± \sqrt{4×13} }{2} = \frac{ - 4±2 \sqrt{13} }{2} = \frac{ 2(-2± \sqrt{13} )}{2} = -2± \sqrt{13}

m1=-2+√13

m2=-2-√13

ПОКАЗАТЬ ОТВЕТЫ